The influence of single-walled carbon nanotubes additives on the structure and hydrogenation behavior of magnesium hydride; Journal of Energy Storage; Vol. 119 - Elman R. R. Roman Romanovich; Kurdyumov N. Nikita; Laptev R. S. Roman Sergeevich; Kudiyarov V. N. Victor Nikolaevich (2025, 2025)
Title screen